Best Practice of Student Exchange in MBKM Program at English Department - Mangalik, Irene; La’biran, Roni; Rachel, Rachel (Universitas Cokroaminoto Palopo, 2023)
The urgency of this research is to find out what students' experiences are during the student exchange program. The purpose of this research is to find out the experience of students participating in student exchanges. The researcher conducted this research using qualitative methods. The purposive sampling strategy was used to obtain data from students of the English Education study program who had participated in the student exchange program. The data was obtained by interview technique. The findings show that experience starts from the preparation, selection, process, and evaluation. In the preparation stage, students seek information through various sources, such as social media. The selection stage involves online tests as well as administrative challenges that are solved with various strategies. The process stage included adaptation to the new environment, communication challenges, and culture shock, which were overcome in various ways, such as learning about the local culture and establishing interactions. Evaluations showed that the experience provided many benefits, including improved mindset, self-confidence, social relationships, academic experience, and greater cultural insight. Experience of students from preparation to evaluation is that students prepare themselves and follow the selection process well, go through a series of processes to find enormous benefits including opening mindsets and broadening their horizons, social interaction of students and can increase understanding of ethnic, religious, racial and cultural diversity. Although there are some challenges faced, students feel that their experience is very valuable and enriches their lives, both in terms of academic, social, and personal.